Adapting to Climate Change in the Upper Mississippi River Basin: Exploring Stakeholder Perspectives on River System Management and Flood Risk Reduction - Tamsen Reed; Lisa Reyes Mason; Christine C. Ekenga (SAGE Publishing, 2020)
In the Midwestern United States (US), river flooding is a climate change-related hazard that poses a significant threat to health, well-being and economic stability. The 2019 Midwest floods led to major flooding at every monitoring site along the Mississippi River, set record water levels at 42 sites, and resulted in an estimated $6.2 billion in infrastructure damage and recovery costs. Although the risks associated with increasing flooding in the Midwestern US have been well recognized, less is known about the adaptation challenges and opportunities in the region, particularly in the Upper Mississippi River Basin. This exploratory study examined stakeholder perspectives on river system management, flood risk reduction, and adaptation planning in the Upper Mississippi River Basin. We conducted in-depth interviews with flood management stakeholders between August and October 2019. Interview data were analyzed using thematic analysis. Five themes emerged from the interviews: (1) River flooding in the Midwestern US is a different experience than US coastal flooding; (2) River flooding in the Midwestern US is a regional experience that requires a regional response; (3) Local actors face constrained resources for flood risk protection and recovery; (4) Differentiated responsibility across levels of governments makes recovery and response difficult to navigate; and (5) Competing stakeholder goals challenge cooperative flood hazard management. Overall, these results suggest that locally focused adaptation efforts, while perhaps appropriate for coastal communities or more urban contexts, are suboptimal strategies for communities in the flood-prone river basins of the Midwestern US. Instead, structures and support for regional collaboration should be considered and pursued.